Favorable spring conditions can buffer the impact of winter carryover effects on a key breeding decision in an Arctic‐breeding seabird. Issue 2 (9th February 2022) - Steenweg, Rolanda J.; Crossin, Glenn T.; Hennin, Holly L.; Gilchrist, H. Grant; Love, Oliver P.
Abstract: The availability and investment of energy among successive life‐history stages is a key feature of carryover effects. In migratory organisms, examining how both winter and spring experiences carryover to affect breeding activity is difficult due to the challenges in tracking individuals through these periods without impacting their behavior, thereby biasing results. Using common eiders Somateria mollissima, we examined whether spring conditions at an Arctic breeding colony (East Bay Island, Nunavut, Canada) can buffer the impacts of winter temperatures on body mass and breeding decisions in birds that winter at different locations (Nuuk and Disko Bay, Greenland, and Newfoundland, Canada; assessed by analyzing stable isotopes of 13‐carbon in winter‐grown claw samples). Specifically, we used path analysis to examine how wintering and spring environmental conditions interact to affect breeding propensity (a key reproductive decision influencing lifetime fitness in female eiders) within the contexts of the timing of colony arrival, pre‐breeding body mass (body condition), and a physiological proxy for foraging effort (baseline corticosterone). We demonstrate that warmer winter temperatures predicted lower body mass at arrival to the nesting colony, whereas warmer spring temperatures predicted earlier arrival dates and higher arrival body mass. Both higher body mass and earlier arrival dates of eider hens increased the probability that birds would initiate laying (i.e., higher breeding propensity). However, variation in baseline corticosterone was not linked to either winter or spring temperatures, and it had no additional downstream effects on breeding propensity. Overall, we demonstrate that favorable pre‐breeding conditions in Arctic‐breeding common eiders can compensate for the impact that unfavorable wintering conditions can have on breeding investment, perhaps due to greater access to foraging areas prior to laying. Abstract : The availability and investment of energy among successive life‐history stages is a key feature of carryover effects. Using common eiders, we used path analysis to examine how wintering and spring environmental conditions interact to affect breeding propensity (a key reproductive decision influencing lifetime fitness in female eiders) within the contexts of the timing of colony arrival, prebreeding body mass (body condition), and a physiological proxy for foraging effort (baseline corticosterone). Overall, we demonstrate that in favorable prebreeding conditions, Arctic‐breeding common eiders can compensate for the impact that unfavorable wintering conditions can have on breeding investment, perhaps due to greater access to foraging areas prior to laying.